Implementasi Strategi Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Pendidikan Agama di SMA Negeri 4 Kendari - Suryanagara Suryanagara (Badan Penerbit STIEPARI Press, 2023)
This study aims to apply problem-based learning strategies to improve student learning outcomes. This study is classified as Classroom Action Research which consists of two cycles. The research was conducted at SMA Negeri 4 Kendari involving 37 class XI students on the material principles and practices of economics in Islam. The research instrument consisted of observation sheets and test sheets with data analysis techniques in the form of descriptive analysis. The study found an increase in learning outcomes between cycles one and two, with a learning completeness percentage of 78%. Therefore, it can be concluded that using problem-based learning strategies can improve student learning outcomes.